2016
DOI: 10.1038/ncomms13139
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of acetate adsorbates drives atomic rearrangement on the Au(110) surface

Abstract: Weak inter-adsorbate interactions are shown to play a crucial role in determining surface structure, with major implications for its catalytic reactivity. This is exemplified here in the case of acetate bound to Au(110), where the small extra energy of the van der Waals interactions among the surface-bound groups drives massive restructuring of the underlying Au. Acetate is a key intermediate in electro-oxidation of CO2 and a poison in partial oxidation reactions. Metal atom migration originates at surface def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 59 publications
(70 reference statements)
2
40
0
Order By: Relevance
“…These findings support spectroscopic measurements which have shown that, independent of the crystal orientation, acetate anions prefer to bind to an Au surface in a bidentate configuration . They are also in agreement with DFT calculations and STM images acquired under UHV conditions for acetate adsorbed on Au(110) . It is not possible, however, from the spectroscopic data to distinguish between specific adsorption sites for the acetate adsorbate.…”
Section: Resultssupporting
confidence: 89%
“…These findings support spectroscopic measurements which have shown that, independent of the crystal orientation, acetate anions prefer to bind to an Au surface in a bidentate configuration . They are also in agreement with DFT calculations and STM images acquired under UHV conditions for acetate adsorbed on Au(110) . It is not possible, however, from the spectroscopic data to distinguish between specific adsorption sites for the acetate adsorbate.…”
Section: Resultssupporting
confidence: 89%
“…The distance between the backbone of the species and the Cu surface increases when the vdW interactions were excluded, confirming the significant vdW effects on the structures. [26][27][28][29][30][31] The transition states for C-H bond breaking of 1-propoxy and 1-butoxy were reexamined with the updated adsorption structures. The NEB calculations suggested that the transition It is important to emphasize more generally the difficulty in finding the global minimum in the high-dimensional configuration space of adsorption for large molecules.…”
Section: Multiple Basins In the Energy Landscape Of Adsorptionmentioning
confidence: 99%
“…Following CO 2 reduction to -CH 2 on the surface of Cu, dimerization of the latter with free CO from Ag would occur to give the C-C bond on the surface. Once formed on the surface, further reduction of acetaldehyde would give acetate as the final product (40).…”
Section: +mentioning
confidence: 99%